Studying Arabic Experience through Language Games to Improve Students’ Learning Motivation in Higher Education - Muhammad Alfan (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2015)
Teaching of Arabic had really spread in Indonesia this lately, both in formal and informal institutions, either at the school, boarding school or university level. But unfortunately the teaching of Arabic from the past until now still faced with various problematic. Among those problems are the low level of student motivation during learning process. The phenomenon of this low motivation is found by the author based of his experience in teaching Arabic at the universities. This phenomenon encouraged the author to devote his attention in order to analyze the problems and provide a solution. After analyzing the problem, the authors found that the problem of low level of student motivation in Arabic teaching has centered on four issues, are:(1) The encouragement and the needs for teaching of Arabic, (2) the expectations and purposes in the future, (3) the learning environment, and (4) the existence of things that are interesting and fun in teaching. This indicates that the level of student motivation in learning Arabic at universities is still low. Therefore the author always thought which raises the spirit and intent to make the development, innovation, design, and improvement in the teaching process. The Author attempts to teaching Arabic with games because it has an important role in improving student motivation and maintain it. Through the individual games, the learners can develop themselves, cognition and interact with their environment. Based on the author's experience, he has tried as many as 21 language games, but in this simple article he convey about 14 games. when the games has been applied, the author found that the level of student motivation during the process of Arabic teaching is increasing.